Plasma Renin Activity and Aldosterone Concentrations in Hypertensive Cats with and without Azotemia and in Response to Treatment with Amlodipine Besylate - Jepson, R.E. (J Vet Intern Med, 2013)
BACKGROUND: Role of renin‐angiotensin aldosterone system (RAAS) in feline systemic hypertension is poorly understood. OBJECTIVES: Examine plasma renin activity (PRA) and plasma aldosterone concentrations (PAC) in normotensive and hypertensive cats with variable renal function and in response to antihypertensive therapy. ANIMALS: One hundred and ninety‐six cats >9 years from first opinion practice. METHODS: PRA, PAC, and aldosterone‐to‐renin ratio (ARR) were evaluated in cats recruited prospectively and grouped according to systolic blood pressure (SBP) and renal function (nonazotemic normotensive [Non‐Azo‐NT], nonazotemic hypertensive [Non‐Azo‐HT], azotemic normotensive [Azo‐NT], azotemic hypertensive [Azo‐HT]). Changes in PRA and PAC were evaluated with antihypertensive therapy (amlodipine besylate). RESULTS: Plasma renin activity (ng/mL/h; P = .0013), PAC (pg/mL; P < .001), and ARR (P = 0.0062) differed significantly among groups. PRA (ng/mL/h) was significantly lower in hypertensive (Non‐Azo‐HT; n = 25, median 0.22 [25th percentile 0.09, 75th percentile 0.39], Azo‐HT; n = 44, 0.33 [0.15, 0.48]) compared with Non‐Azo‐NT cats (n = 57, 0.52 [0.28, 1.02]). Azo‐HT cats had significantly higher PAC (n = 22, 149.8 [103.1, 228.7]) than normotensive cats (Non‐Azo‐NT; n = 26, 45.4 [19.6, 65.0], Azo‐NT; n = 18, 84.1 [38.6, 137.8]). ARR was significantly higher in Azo‐HT (n = 20, 503.8 [298.8, 1511]) than Azo‐NT cats (n = 16, 97.8 [77.0, 496.4]). Significant increase in PRA was documented with antihypertensive therapy (pretreatment [n = 20] 0.32 [0.15–0.46], posttreatment 0.54 [0.28, 1.51]), but PAC did not change. CONCLUSIONS AND CLINICAL IMPORTANCE: Hypertensive cats demonstrate significantly increased PAC with decreased PRA. PRA significantly increases with antihypertensive therapy. Additional work is required to determine the role of plasma aldosterone concentration in the pathogenesis of hypertension and whether this relates to autonomous production or activation of RAAS without demonstrable increase in PRA.